William Walton’s pursuit of compositional independence in the Three songs from Edith Sitwell - Steinberg, Nicole (My University, 2019)
[From Introduction] Over a career of sixty-six years, William Walton established himself as a staple composer of the English twentieth century. However, Walton spent the first seventeen years of that career traveling a rather crooked path of experimental failures before Symphony No. 1 premiered in 1934, elevating his status to that of an independent composer competitive on the international stage. This paper casts new light on the importance of the Three Songs from Edith Sitwell (1932) in the output of Walton before his breakthrough with Symphony No. 1. In contrast to the existing scholarship on the Three Songs from Edith Sitwell, this work examines the historical and compositional implications of this set in the context of the works that came both before and after its publication. The latter two songs of the set, “Through Gilded Trellises” and “Old Sir Faulk,” are almost direct transcriptions from the Façade Entertainment, a compositionally and socially experimental piece he worked on extensively in 1922 with creative input from the Sitwell siblings. They represent the earlier and more experimental period in Walton's development, exhibited by their use of post-tonal methods. The first song of the set, “Daphne,” though he had set the poem in a previous cycle, was conceived as a completely new setting to be written in the style which Walton had begun to establish at the latter part of the 1920s. Therefore, it contains the neo-romantic idiom of Walton's later career as demonstrated in his Viola Concerto (1929) and Belshazzar’s Feast (1931). Walton emphasizes the dichotomy of these two periods of his life by compiling all three pieces into a set. However, by placing “Daphne” first, Walton announces the codification of his neo-romantic style that would permeate the rest of his career. As the First Symphony was premiered just over a year later, the importance of Three Songs from Edith Sitwell cannot be ignored. Through a comprehensive historical and analytical study of the aforementioned pieces, it becomes evident how the Three Songs from Edith Sitwell helped Walton to achieve an independence from the Sitwells that would lead to the explosion of his international career.
(M.M.) -- Towson University, 2018. Link to Master's Recital Recording: https://www.youtube.com/watch?v=UYtFF5rrNS4